(Non‐)Participation in deliberation at work: a case study of online participative decision‐making. (28th January 2019) - Schiavo, Gianluca; Villafiorita, Adolfo; Zancanaro, Massimo
Abstract : Social media are implemented by organisations to enhance productivity and knowledge sharing among employees, but they can also support group deliberation and employee voice. This paper presents a case study of an online deliberation initiative involving the discussion of a contentious internal policy within an organisation of around 550 knowledge workers. The deliberation process lasted 5 weeks and actively involved 167 employees. Different sources of information (user interaction logs, activity patterns, questionnaire responses) were analysed to investigate the impact of participation, or non‐participation, on the level of satisfaction with the deliberation, and on the understanding of the issue discussed. The findings suggest that (1) interest is a driver for participation, but it does not explain active participation, (2) participation, either active or passive, positively influences the understanding of the issue and (3) satisfaction with the outcome is not related to participation, but it may support participation in future initiatives.